Alergi susu sapi - Mulya Safri (Jurnal Kedokteran Syiah Kuala, 2008)
Daftar pustaka1.     Lifsehitz   C,   Alergy   to  cow  milk.  J.Ped.  Neonatal 2005;2:1-7.2.   Muraro   A,   Dreborg   S,    Halken   S  et   al,   Dietary prevention  of  allergic  diseases  in  infant  and  small children  Part  Ill:   Critical  review  of published  peer-reviewed   observational    and interventional studies and final    recommendation.    Pediatr   Allergy Immunol,2004; 15:291-3073.   Sampson HA.  Adverse reactions  to foods.Dalam: Middleton   E,  Reed CE, Elliot  EF, Adkinson NF, Yunginger JW,  Busse  WW, penyunting.  Allergy, Principle   and  Practice.Edisi   ke-4.St.Louis,   Mosby,1993:h    1661-   86.4.     Host  A.   Halken   S. Approach  to  feeding problems in the    infant    and  young  child.    Dalam:  Leung  DYM, Sampson      HA,    Geha   RS,    Szefler   SJ,   penyunting. Pediatric     Allergy   principles    and  practice.  Missouri, Mosby, 2003.h.488-94.5.   Ebisawa   M,    Sugizaki     C,  Ikeda   Y,  Tachimoto  H.Development    of  food  allergy  during  infancy. APAPARI-KAPARD   Joint   congress.  Seoul,  Korea. April 2005.6.     Sampson HA.Food allergy.   Part I:lmmunopathogenesis    and clinical disorders. J.Allergy   Clin lmmunol   1999;103:717-287.     Burks AW, James JM,Hiegel   A,Wilson G, et al.Atopic  dermatitis and food hypersensitivity reactions. J Pediatr  1998;132:132-68.     Sicherer   Sh,Sampson   HA.Food hypersensitivity and atopic dermatitis:  Pathofysiology,  epidemiology, diagnosis and management  J Allergy Clin lmmunol1999;   104:Sl  14-sl229.    Hill  DJ,  Duke AM,  Hosking  CS,et al.Clinical manifestations of cow's  milk allergy in childhood:II.The  diagnosis  value of skin tests and RAST. Clin Allergy 1988;18:481-9010.   William LW, Bock SL. Skin testing and food challenges  for evaluation of food allergy. Immunology and Allergy Clinics of North Amer 1999;19:479-931 L  Bishop MJ,  Hasting.  Naturai history of cow's milk allergy. Clinical outcome.  J Pediatr 1990;116:862-7.12.  Vanto  T,  Helpplia  S,   Juntunen-Backman  K, Kalimo K, Klemola  T, Korpela  R. Prediction of the development  of  tolerance  to  milk  in  children  with cow's  milk hypersensitivity.   J Pediatr 2004;144:218-2213.  Eggesbo M, Halvorsen R, Tambs K. Prevalence of parentally perceived adverse reaction to food in young children.  Pediatr Allergy lmmunol  1999;10:122-32.14.   Host A., Halken S. A prospective study of cow's milk alergy in Danish infants during the first 3 years of life. Alergy 1990;45:587-96.15.   Hest A. Cow's  milk protein alergy and intolerance in infancy.      Some     clinical,      epidemiological     and immunological    aspects.    Pediatr   Allergy   lmmunol1994;5:l-3